Dioramas as Multimodal Instructional Media in English Language Education: A Literature Review - Kakerissa, Wenda Marlin; Meyer, Fredi (Koli Journal : English Language Education, 2025)
In the domain of learning English as a foreign language, there are ongoing discussions regarding the effectiveness of visual learning media in developing contextual and meaningful language skills. This study presents Jewitt and Mayer’s multimodal learning theory, Kolb’s experiential learning theory, and project-based learning approaches as analytical frameworks for exploring the role of dioramas in language instruction. The three theories emphasize that learning experiences are enhanced when students engage through multiple channels of representation (visual, linguistic, spatial) and actively participate in creating meaning through collaborative projects. An extensive review of the literature from the past five years indicates that dioramas effectively enhance contextual vocabulary acquisition, improve both oral and written language production, foster critical thinking, and promote cultural awareness. Dioramas are recognized as effective and practical tools that can be employed across various educational levels and are adaptable to advancements in technology. Theoretical implications indicate that the use of dioramas as a pedagogical method in English language education can be effective when thoughtfully integrated into the curriculum, supported by comprehensive teacher training, and supplemented with pertinent guides addressing both local and global issues.